METODE TAFSIR NAFAHÃT AL-QURâÃN KARYA NÃSHER MAKÃREM AL-SYÃRÃZÃ - Yuliarto, Udi (LP2M IAIN Mataram, 2011)
One of the most important works in Qurâanic exegesis that employs a thematic approach is TafsÃ®r NafahÃ¢t al-QurâÃ¢n UslÃ»b JadÃ®d fÃ® al-TafsÃ®r al-MaudlÃ»âÃ® li al-QurâÃ¢n al-KarÃ®m, authored by NÃ¢sher MakÃ¢rem al-SyÃ®rÃ¢zÃ®. The study seeks to elucidate the methodology of exegesis employed in the work. Thematic approach of the Qurâan (tafsir al-maudlÃ»âÃ®) has developed significantly and showed diverse models in terms of the pattern of interpretation and theme. The author of the work, al-SyÃ®rÃ¢zÃ®, offers a new approach in thematic exegesis, which significantly differs from that introduced by al- FarmÃ¢wÃ®, whose model of interpretation has so far dominated the field. Al-SyÃ®rÃ¢zÃ® thus opens pathways for reform of Qurâanic exegesis. His approach is built on the Syiâi theological doctrine of the five principles, namely knowing God and Oneness of God, Prophethood, Leadership, Eschatology and Justice. The adoption of these principles in the work of al-SyÃ®rÃ¢zÃ® has created a distinctive nuance of Qurâanic exegesis, which is rational and comprehensive.